Hungarian Monitoring, 13 September 1989 . [Magyar rádiófigyelő], 1989. szeptember 13 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Yeltsin's US schedule - Situation in Poland - East German refugees - H. Kohl re-elected as party chairman Domestic Affairs: - Hungarian Socialist Workers' Party (MSZMP) Central Committee closed session - Three-sided political conciliation talks - Viktor Orbán's Zalaegerszeg speech - According to Iván Vitányi, change of system is required instead of change of model Külpolitika: - Jelcin Egyesült Államokbeli programjáról - Lengyelországi helyzet - Kelet-német menekültek ügye - H. Kohlt újraválasztották a pártelnöki tisztségre Belpolitika: - MSZMP KB zárt ülése - Háromoldalú politikai egyeztető tárgyalások - Orbán Viktor zalaegerszegi beszéde - Vitányi Iván szerint rendszerváltásra van szükség a modellváltás helyett